2017
DOI: 10.1002/jmr.2612
|View full text |Cite
|
Sign up to set email alerts
|

In silico characterization of enantioselective molecularly imprinted binding sites

Abstract: A 2-step molecular mechanical and quantum mechanical geometry optimization scheme (MM ➔ QM) was used to "computationally imprint" chiral molecules. Using a docking technique, we show the imprinted binding sites to exhibit an enantioselective preference for the imprinted molecule over its enantiomer. Docking of structurally similar chiral molecules showed that the sites computationally imprinted with R- or S-tBOC-tyrosine were able to differentiate between R- and S-forms of other tyrosine derivatives. The cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Although the LOD is not so low as in other published works ( Table 1 ), those methodologies are mostly non electroanalytical but mainly based in a chromatographic separation, which makes this alternative particularly advantageous in terms of portability and speed. It is worth mentioning that this study was performed using a racemic mixture, however recent studies are showing that the S enantiomer is more potent than the R [ 116 ], thus this is something that should be addressed in future electroanalytical studies including in the theoretical simulation step [ 117 , 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the LOD is not so low as in other published works ( Table 1 ), those methodologies are mostly non electroanalytical but mainly based in a chromatographic separation, which makes this alternative particularly advantageous in terms of portability and speed. It is worth mentioning that this study was performed using a racemic mixture, however recent studies are showing that the S enantiomer is more potent than the R [ 116 ], thus this is something that should be addressed in future electroanalytical studies including in the theoretical simulation step [ 117 , 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the most common use of electronic structure-determining methods in MIP studies for characterization of template–monomer complexes, as discussed above, is to find the most suitable functional monomer and often also the optimal stoichiometry. Of the electronic structure-determining methods, semi-empirical strategies are less demanding on computational resources, and the two most commonly used semi-empirical methods for MIP development are AM1 [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ] and PM3 [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ], while other examples are less common [ 128 , 129 , 130 ].…”
Section: The Pre-polymerization Stagementioning
confidence: 99%
“…Despite the dramatic development of computer hardware and software, multimolecular simulations involving multiple copies of monomers, template and explicit solvent are still not feasible for electronic structure methods alone. However, several examples report the combined use of quantum chemical calculations and MD simulations to study different aspects of pre-polymerization mixtures [ 128 , 143 , 215 , 216 , 392 , 393 , 394 ].…”
Section: The Pre-polymerization Stagementioning
confidence: 99%
“…The simulation results showed that the binding energy of octopamine and 4-vinyl benzoic acid was the smallest. Furthermore, a two-step method of MM and QM were used to simulate the design of enantioselective tBOC-tyrosine imprinted polymers [ 124 ]. The geometric structure of the molecule was greatly optimized after the two-step simulation calculations from the MM method to the MD method.…”
Section: Computational Simulation and Design Of New Mipsmentioning
confidence: 99%